2023
DOI: 10.3389/fcell.2023.1098482
|View full text |Cite
|
Sign up to set email alerts
|

Roles of STAT3 in the pathogenesis and treatment of glioblastoma

Abstract: Glioblastoma (GBM) is the most malignant of astrocytomas mainly involving the cerebral hemispheres and the cerebral cortex. It is one of the fatal and refractory solid tumors, with a 5-year survival rate of merely 5% among the adults. IL6/JAK/STAT3 is an important signaling pathway involved in the pathogenesis and progression of GBM. The expression of STAT3 in GBM tissues is substantially higher than that of normal brain cells. The abnormal activation of STAT3 renders the tumor microenvironment of GBM immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 145 publications
0
15
1
Order By: Relevance
“…Intriguingly, some forms of HIES have been shown to arise from dominant negative mutations in the signaling transduction and activator of transcription 3 (STAT3) gene 27 , which has been linked to many cancers including glioma 28,29 . While the role of STAT3 and the JAK/STAT pathway has been well studied in IDH-WT GBMs [30][31][32] , its significance in IDH-MT glioma is less clear. Further research is needed to investigate the etiologic role of IgE in gliomagenesis, its interaction with genomic alterations and its potential as a therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, some forms of HIES have been shown to arise from dominant negative mutations in the signaling transduction and activator of transcription 3 (STAT3) gene 27 , which has been linked to many cancers including glioma 28,29 . While the role of STAT3 and the JAK/STAT pathway has been well studied in IDH-WT GBMs [30][31][32] , its significance in IDH-MT glioma is less clear. Further research is needed to investigate the etiologic role of IgE in gliomagenesis, its interaction with genomic alterations and its potential as a therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary the correction of STAT-3 enhanced signaling, repressed tumor incidence irrespective of T cell recruitment, MASH, and fibrosis ( Grohmann et al, 2018 ). Interestingly, a growing body of evidence renders STAT-3 signaling a pivotal mechanism in developing various malignancies ( Poser et al, 2019 ; Fu et al, 2023 ). Grohmann et al highlights that the recruitment of T cells and the development of MASH and fibrosis are not mandatory for developing HCC in obesity.…”
Section: T Cells and The Mash- Hcc Transitionmentioning
confidence: 99%
“…[ 87 ] In addition, studies have shown that IL‐6 induces a reciprocal STAT3 activation loop, where IL‐6 released from GBM cells stimulates STAT3 activation which, in turn, results in the upregulation of IL‐6 generation in the astrocytes within the tumor microenvironment. [ 88 ] This enhanced IL‐6 level further activates STAT3 in GBM cells, promoting tumor growth, apoptosis resistance, migration, and invasion. [ 88 ] As such, these findings indicate that targeting STAT3 via IL‐6 could potentially be used as an approach to suppress GBM invasion and tumor growth.…”
Section: Recent Advances In Understanding the Bbb And Its Implication...mentioning
confidence: 99%
“…[ 88 ] This enhanced IL‐6 level further activates STAT3 in GBM cells, promoting tumor growth, apoptosis resistance, migration, and invasion. [ 88 ] As such, these findings indicate that targeting STAT3 via IL‐6 could potentially be used as an approach to suppress GBM invasion and tumor growth. For instance, Chen et al have recently developed polyglycerol‐nano‐diamonds loaded with the anticancer drug DOX, which were specifically designed to target glioma cells while simultaneously inhibiting STAT3 activation and reducing their IL‐6 expression from astrocytes.…”
Section: Recent Advances In Understanding the Bbb And Its Implication...mentioning
confidence: 99%
See 1 more Smart Citation